2018
DOI: 10.1038/s41598-018-29335-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of field- and chamber-grown samples of Colobanthus quitensis (Kunth) Bartl, an Antarctic flowering plant

Abstract: Colobanthus quitensis is one of the two vascular plants inhabiting the Antarctic. In natural habitats, it grows in the form of a cushion or mats, commonly observed in high latitudes or alpine vegetation. Although this species has been investigated over many years to study its geographical distribution and physiological adaptations to climate change, very limited genetic information is available. The high-throughput sequencing with a de novo assembly analysis yielded 47,070 contigs with blast-hits. Through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…However, Pseudomonas strains isolated so far from Antarctic territory have not shown these metabolic capabilities, and even though they can metabolize various C6 carbon sugars, none of them are able to catabolize xylose or arabinose (Lustman et al, 2015; Lee et al, 2017). Most likely, the MPC6 strain has evolved the genetic repertory to metabolize these sugars (C6 and C5), glycerol, organic acids, and aromatic compounds in part due to the fact that Deception Island, where this bacterium was isolated, has one of the largest reservoir of the Antarctic flowering plants Deschampsia Antarctica and Colobanthus quitensis (Komárková et al, 1985); self-fertilizing species that grow as cushions and mats, respectively (Cho et al, 2018) and might provide these carbon substrates. By analyzing the particular environmental and geographical conditions present at the Deception Island, it is possible to decipher and give a concise explanation of the observed genetic traits of strain MPC6.…”
Section: Discussionmentioning
confidence: 99%
“…However, Pseudomonas strains isolated so far from Antarctic territory have not shown these metabolic capabilities, and even though they can metabolize various C6 carbon sugars, none of them are able to catabolize xylose or arabinose (Lustman et al, 2015; Lee et al, 2017). Most likely, the MPC6 strain has evolved the genetic repertory to metabolize these sugars (C6 and C5), glycerol, organic acids, and aromatic compounds in part due to the fact that Deception Island, where this bacterium was isolated, has one of the largest reservoir of the Antarctic flowering plants Deschampsia Antarctica and Colobanthus quitensis (Komárková et al, 1985); self-fertilizing species that grow as cushions and mats, respectively (Cho et al, 2018) and might provide these carbon substrates. By analyzing the particular environmental and geographical conditions present at the Deception Island, it is possible to decipher and give a concise explanation of the observed genetic traits of strain MPC6.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, C. quitensis has an abundant amount of CaOx crystals in its leaves. Moreover, C. quitensis , apart from its tolerance to extreme environmental conditions [ 19 ], represents a highly suitable plant model for the evaluation of the AP mechanism disposing three basic features that have been associated with the AP process: (1) a considerable amount of crystals with dimensions appropriate for accurate measurements of crystal properties (large idioblasts about 50 μm in diameter [ 17 , 18 ]), (2) the presence of transcripts with a high similarity to germin-like proteins (OxO enzymes) in the transcriptome [ 20 , 21 ], and (3) high CO 2 diffusion limitations [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Application of RNA-seq to non-model species allows the use of their transcriptomes to understand their responses to changes in the environment [24, 25]. Many studies clearly demonstrated/ suggested that adaptive plasticity can processed through transcriptome variation [2629], and much work is needed in these regards.…”
Section: Introductionmentioning
confidence: 99%